Intramuscular Tranexamic Acid Administration on the Battlefield. (13th October 2022) - Steele, David; Ballard, P. Kjell; Burke, Riley; Ferguson, Brian
Abstract : Background. Tranexamic acid (TXA) is routinely administered intravenously (IV) and intraosseously (IO) in response to exsanguination. Case. This report describes a patient who sustained multiple high-powered rifle gunshot wounds that received battlefield-environment intramuscular (IM) administration of TXA due to inability to obtain IV / IO access. This case represents the unlikely positive outcome in the setting of multiple remarkable obstacles, which may have been ameliorated by novel administration of TXA. Conclusion. Cases of IM TXA administration as a primary intervention are not well represented in the current body of medical literature. This case report highlights a clinical scenario where IM TXA was utilized as part of first-line treatment that led to a positive clinical outcome. Although IM TXA is not yet endorsed by current trauma guidelines, this case suggests that IM route administration of TXA should be further investigated. If indeed IM administration of TXA proves just as efficacious as alternative routes, this would hold considerable advantageous implications for austere situations were sterility and IV / IO placement are impractical. This would also represent another avenue by which to decrease the time-to-TXA for patients, allowing sooner correction of hemorrhage and trauma-associated coagulopathy.